KONSTRUKSI SOSIAL PENDIDIKAN MASYARAKAT ADAT BADUY - Gabriel, Gabriel; Nugroho, Wahyu Budi; Kamajaya, Gede; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
SOCIAL CONSTRUCTION OF EDUCATION BADUY: ANALYSIS OF EXTERNALIZATION, OBJECTIVATION AND INTERNALIZATION This research aims to analyze the social construction of education in Baduy community in Kanekes Village, Banten. Formal education is a process of basic survival capital to face the world. Education gives a person knowledge, competence, methods, and data. Thus, by taking formal education, individuals can develop their insights and potentials for the continuation of the individual's life. It is different in the Baduy tribe forbidding their community to get formal education, they have a view that if they go to formal school, it will threaten the customs of the Baduy community due to controlled freedom in the outside world. The taboo on formal education does not mean that the Baduy community does not reject science, observation in the field turns out that the Baduy community has a customary education system in accordance with customs or pikukuh karuhun. The method used in this research is a qualitative approach with a descriptive type. The theoretical analysis used as a scalpel in this research is the concept of externalization, internalization, and objectivation according to Peter L. Berger and Thomas Luckmann. The result of this research reveals that the construction of Baduy traditional education is called ngolah which is adjusted to the customs of the Baduy community. Ngolah prioritizes the applicable customary law and has the purpose of passing on ancestral cultural values. Ngolah takes place from generation to generation through family and traditional leaders with the focus of learning on agricultural aspects, cultural values, and the rules of Baduy customs. Thus, ngolah can strengthen the customs of Baduy community in facing the influence of modernization from an early age.   Keywords: Education, Baduy, Social Construction